Biocompatible magnetic tris(2-aminoethyl)amine functionalized nanocrystalline cellulose as a novel nanocarrier for anticancer drug delivery of methotrexate. (10th February 2017) - Rahimi, Mahdi; Shojaei, Salman; Safa, Kazem D.; Ghasemi, Zarrin; Salehi, Roya; Yousefi, Bahman; Shafiei-Irannejad, Vahid
Abstract : A smart, pH-responsive and biocompatible nanocarrier, aimed to achieve an efficient targeted drug delivery system, was facilely synthesized. Abstract : In cancer therapy, biocompatible and smart nanocarriers are the most important types of therapeutic agents. In this paper, a novel magnetic nanocarrier was fabricated and investigated for controlled release of methotrexate (MTX). A magnetic nanocarrier was synthesized by decoration of Fe3 O4 nanoparticles using biocompatible tris(2-aminoethyl)amine functionalized nanocrystalline cellulose (AMFC). AMFC coated magnetic nanoparticles (AMFC@MNPs) were characterized by various technologies including FTIR, SEM-EDX, VSM, XRD, DLS and zeta potential analysis. MTX was loaded on the nanocarrier at physiological pH (7.4) due to the hydrogen bonding and electrostatic interactions between cationic amino groups on the nanocarrier and anionic carboxylate groups of MTX molecules. The MTX release ability of the synthesized nanocarrier was proved through the comparison of in vitro drug release under simulated physiological and tumor tissue conditions. The cumulative release of the MTX-loaded nanocarrier was pH dependent with a superior release rate at pH 5.4. The results of MTT assay and DAPI staining showed that the MTX-loaded nanocarrier revealed a high cytotoxicity in the MCF7 breast cancer cell line after 48 h incubation. Also, the results of cytotoxicity and hemolysis assays have shown that there are negligible toxicity and hemolytic effects of AMFC@MNPs at high concentrations. Therefore, it was concluded that our nanocarrier has many promising advantages as an efficient carrier for the targeted MTX delivery to the cancer cells.